Estudo de relações ecodoplercardiográficas, eletrocardiográficas, ultrassonográficas e radiológicas em pacientes renais crônicos - Loureiro, Afonso Augusto Carvalho (1995)
Forty patients with end stage renal disease, twenty hipertensives and twenty healthy persons comprised the object of the authors s survey. Ecocardiography has shown to be the earliest and most sensitive method of heart enlargement in patients with hypertensive disease. Rx and Ecg are easily done although not sensitive. The authors s choice of ecocardiography as the simpliest and accurate method of ventricular hypertrophy is in accordance with literature data.